The Effect of Using Wordwall Application on 11th Graders' Speaking Skill at SMAN 1 Ciruas - Ghina Fadhila; Syafrizal; Eri Rahmawati (Jurnal Ilmiah Multidisiplin Nusantara (JIMNU), 2026)
This research was undertaken to analyze the influence of the Wordwall application on the speaking skills of eleventh-grade students at SMAN 1 Ciruas. Consequently, Wordwalluantitative methodology and a quasi-experimental design involving 82 participants, organized into two equally sized groups, namely the experimental and control groups. Data collection was conducted through speaking assessments administered prior to and following the treatment. The findings showed that students who received the treatment achieved better improvement in speaking skills than those in the control group. The average score achieved by the experimental group increased from 63.90 to 83.12, whereas the control group’s mean score rose from 66.15 to 74.34. The hypothesis test results revealed a significance value below 0.05 (p < 0.001), providing evidence of a statistically significant difference between the groups. The results point to the fact that the Wordwall application was effective in enhancing students’ speaking skills.. Consequently, Wordwall can be considered an effective technology-based learning tool for promoting speaking skill development in English language learning.